Women, Marriage, Housekeeping, and Religious Upbringing of Children in Islamic Thought - Maryam Ahmad pour (Islām va ̒ulūm-i ijtimā̒ī)
The present article is concerned with the concept analysis of marriage, religious upbringing of children, which naturally comes after family formation, based on two main sources of Islam viz. the Quran and Sunnah. Theoretical basis of this research study consists of a variety of feminist theories. Its methodology is based on documentation, analysis of findings, discovering marriage implications, housewifery, religious upbringing in the Quran and Sunnah. The findings suggest that Islamic views (viz. the Quran and Sunnah) regarding marriage, domestic labor and religious upbringing are in conflict with feminist theories. Holy Quran and religious traditions view these phenomena through a mechanism far from feminist paradigm. According to Islamic thought the most important principle for women is that they pay attention to their functions in the family as a mother or a wife. Special attention also has been paid to the most important functions of marriage and family, that is to say instinctive and emotional needs, creating an environment fraught with ethical and moral virtues, promotion of excellence in both sexes and in the religious upbringing of children. Results also show that Islam is an institution that has taken into consideration all aspects of human life. Thus such a religious upbringing of children will encompass all aspects of social, ethical and sexual education of children.